Stop staring : facial modeling and animation done right - Osipa, Jason (Indianapolis, Ind. : Wiley Pub., 2010)
'The de facto official source on facial animation--now updated! If you want to do character facial modeling and animation at the high levels achieved in today's films and games, Stop Staring: Facial Modeling and Animation Done Right, Third Edition, is for you. While thoroughly covering the basics such as squash and stretch, lip syncs, and much more, this new edition has been thoroughly updated to capture the very newest professional design techniques, as well as changes in software, including using Python to automate tasks. Shows you how to create facial animation for movies, games, and more. Provides in-depth techniques and tips for everyone from students and beginners to high-level professional animators and directors currently in the field. Features the author's valuable insights from his own extensive experience in the field. Covers the basics such as squash and stretch, color and shading, and lip syncs, as well as how to automate processes using Python. Includes a CD with sample projects from the book, models, and textures. Breathe life into your creations with this important book, considered by many studio 3D artists to be the quintessential reference on facial animation.'--
Includes index.
Keywords: Computer animation; Computer graphics; Facial expression in art